2020
DOI: 10.1177/0300060520913149
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of and reference ranges for peripheral blood lymphocytes and CD4+ T cell subsets in healthy adults in Shanxi Province, North China

Abstract: Objective To guide clinical decision making, race-, age- and gender-specific reference ranges for lymphocytes and CD4+ T-cell subsets are required. Methods Single platform flow cytometry to determine reference intervals for lymphocyte subpopulations and CD4+ T-cell subsets in 196 healthy Han Chinese adults. Results The frequencies and absolute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…These discrepancies could be attributed to differences in study design, population and distribution of confounding factors. Some studies [ 43 45 ] have suggested that hormones and cytokines could affect CRP, IL-10 and CD4/CD8 levels, but the underlying physiological mechanisms remained unclear. Further studies with larger sample sizes were needed to confirm our results and to conclude whether there was a gender difference in the effects of HRSV A and B on CRP, IL-10 and CD4/CD8 rate.…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies could be attributed to differences in study design, population and distribution of confounding factors. Some studies [ 43 45 ] have suggested that hormones and cytokines could affect CRP, IL-10 and CD4/CD8 levels, but the underlying physiological mechanisms remained unclear. Further studies with larger sample sizes were needed to confirm our results and to conclude whether there was a gender difference in the effects of HRSV A and B on CRP, IL-10 and CD4/CD8 rate.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, both the absolute number and the percentage of CD4+ T cells, CD8+ T cells, and the CD4/CD8 ratio did not differ between the active and the nonactive group. In peripheral blood, CD4+T cells and CD8+T cells are the main lymphocytes with a huge number [ 26 ].Thus, a small amount of cells migrating and infiltrating in the orbit may not be enough to change the absolute number and the percentage of these cells. As the same, the absolute number and percentage of total lymphocytes did not differ between the active and the non-active group, which is consistent with the report of Ionni [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…DPT cells are mainly present in the thymus and further differentiate into CD4+ or CD8+ T cells [ 28 ]. Recently, DPT cells were also found in the orbital connective tissue of patients with active TAO by immunohistochemical analysis [ 26 ]. While in our study, no significant difference was found in peripheral blood DPT cells between the active and the nonactive group.…”
Section: Discussionmentioning
confidence: 99%
“…Cell Quest software was used to analyze CD4 + T‐cell subset frequencies. Absolute numbers of various CD4 + T subsets were calculated by multiplying the percentage of each CD4 + T subset by the total number of CD4 + T cells 13–15 . The phenotypic characteristics of lymphocytes and CD4 + T cell subsets are shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%